Implementasi Layanan Kesehatan, Gizi, dan Perawatan dalam Menanamkan Disiplin Hidup Sehat (PIAUD IAIN Kudus, 2021)
Early childhood health services, have routine activities of washing hands, maintaining personal health and protecting the environment. Nutritional services have routine activities, namely the provision of balanced nutritional meals in schools. Care services have first aid management and control the child's physical condition (body temperature and injuries). However, in reality there is no balance between school and home, while schools implement health, nutrition and care services. This research was conducted to familiarize yourself with health, nutrition and care services at An-Nur Cirebon PAUD; early childhood healthy life discipline; and the results of instilling the discipline of healthy life in early childhood. This research uses qualitative descriptive research, this research was chosen because it wanted to reveal more detail and clearly about health services, nutrition, care in instilling the discipline of a healthy life at PAUD An-Nur Cirebon. This research data collection technique is divided into 3 parts, namely observation, interviews, and documentation. The data analysis technique of this research is divided into 2, namely data reduction and triangulation. Keywords: Health Services, Nutrition, Nursing, and Healthy Living Disciplines.